2020
DOI: 10.1136/bmjopen-2020-038421
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality post gynaecological cancer treatment: a qualitative study with South African women

Abstract: ObjectivesThis study investigated women’s experiences of their sexuality post gynaecological cancer treatment. Using a holistic sexuality framework, the study explored how women felt their sexual functioning, sexual relationships and sexual identity had been affected by treatment.DesignThe study was qualitative in nature and made use of an interpretive descriptive design. Data were analysed using thematic analysis.SettingData collection took place at a follow-up clinic within the gynaeoncology unit at a public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…Majority of the women in this study reported changes in their sexual functioning before and after therapy, including a significant disruption in their sexual lives as a result of severe symptoms and/or treatment side effects. For instance, symptoms such as heavy bleeding, unpleasant discharge and weariness are common in late-stage gynaecological cancers and might influence a woman’s sexuality beyond the therapy and post-treatment periods 2…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Majority of the women in this study reported changes in their sexual functioning before and after therapy, including a significant disruption in their sexual lives as a result of severe symptoms and/or treatment side effects. For instance, symptoms such as heavy bleeding, unpleasant discharge and weariness are common in late-stage gynaecological cancers and might influence a woman’s sexuality beyond the therapy and post-treatment periods 2…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers may be able to assist patients with their psychosexual recovery, because when a healthcare expert legitimises sexuality themes in a therapy setting it allows individuals and couples to discuss them on their own. This could lead to more open discussions about sexual issues, as well as a reduction in marital conflict and sexual violence 2. Healthcare workers who work with patients with gynaecological cancer should strive to improve their understanding of sexuality in the setting of cancer by reading relevant materials and attending workshops and conferences 2 21 22…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations